MDSolution research treats industrial waste-water into clean water - UMP, PNC (2019)
Concern about the environmental impact arising from industrial waste, researcher from the Faculty of Technology Engineering (FTeK) at Universiti Malaysia Pahang (UMP), Dr. Nadzirah Mohd Mokhtar, took the initiative to invent a membrane distillation system to treat waste-water from several industries, like rubber, palm oil and textile factories, and food and beverage.